Brainstem Auditory Evoked Potentials in Boys with Autism: Still Searching for the Hidden Truth - VERVERI, Athina; VARGIAMI, Euthymia; PAPADOPOULOU, Vassiliki; TRYFONAS, Dimitrios; ZAFEIRIOU, Dimitrios I (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Ververi A, Vargiami E, V Papadopoulou V, Tryfonas D, Zafeiriou DI. Brainstem Auditory Evoked Potentials in Boys with Autism: Still Searching for the Hidden Truth. Iran J Child Neurol. Spring 2015;9(2):21-28. Abstract Objective Brainstem auditory evoked potentials (BAEPs) have long been utilized in the investigation of auditory modulation and, more specifically, auditory brainstem functions in individuals with autism. Although most investigators have reported significant abnormalities, no single BAEPs pattern has yet been identified. The present study further delineates the BAEPs deficits among subjects with autism. Materials & Methods BAEPs were recorded in 43 male patients, aged 35–104 months, who underwent standard evaluations after receiving a diagnosis of autism. The control group consisted of 43 age-matched typically developing boys. The study took place in a tertiary neurodevelopmental center over a period of two years. Results The mean values of all absolute and/or interpeak latencies were longer in patients when compared to controls, albeit the differences were not significant for any of the parameters. Prolonged or shortened absolute/interpeak latencies (control group mean ± 2.5SD) were unilaterally or bilaterally identified in 33% of patients, compared to 9% of controls. The most frequent findings included prolongation of absolute latencies I, V and III, followed by shortening of interpeak latency I-V. In addition, abnormalities (either shortening or prolongation) of absolute latencies I and V, as well as interpeak latency I-V, were significantly more common among patients. Taken together, BAEPs in 23% of patients were indicative of a clinically abnormal response in 32% of patients. Conclusion As can be easily concluded, BAEPs abnormalities characterize only a subset of subjects with autism, who may be important to identify clinically. The latter individuals may benefit from targeted intervention to utilize brainstem plasticity.